OMBUDSMAN: STUDI PERBANDINGAN HUKUM ANTARA INDONESIA DENGAN DENMARK - Fikri, Sultoni; Hadi, Syofyan (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
The Ombudsman as a state institution has the duty to oversee the administration of the state, particularly in public services in order to realize good governance. Therefore the institution is demanded to be independent and impartial to other state institutions. In addition, the presence of the Ombudsman becomes a manifestation of legal protection for the community in the event of maladmnistration conducted by the apparatus/state officials in using their authority. The birth of the Ombudsman is inseparable from history in Scandinavian countries, including in Denmark. The Danish Ombudsman, known as the Folketingets Ombudsmand, has become one of the most important institutions in the state system there. While in Indonesia, its position has received less attention. This difference makes the writer interested to compare it. The approach used in this paper uses a micro-type body of norm approach, which is a legal comparison that uses the Act as the basis for comparison, which is used is Act Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia compared to the Danish Ombudsman Act. Whereas the legal comparison method uses analytical method. The result of this research is to reconstruct the law in Law Number 37 Year 2008 concerning the Ombudsman of the Republic of Indonesia by adopting from what is in the Danish Ombudsman Act. the hope is that the existence of ORI is so respected and recommendations from ORI are not merely morally binding but are legally binding.Ombudsman sebagai lembaga negara yang memiliki tugas untuk mengawasi dari penyelenggaraan negara, khususnya pada pelayanan publik agar terwujudnya good governence. Oleh karena itu lembaga tersebut dituntut untuk bersifat independen dan tidak memihak kepada lembaga negara lainnya. Selain itu hadirnya Ombudsman menjadi suatu perwujudan perlindungan hukum bagi masyarakat apabila terjadi maladmnistrasi yang dilakukan oleh aparatur/pejabat negara dalam menggunakan kewenangannya. Lahirnya Ombudsman tidak lepas dari sejarah di negara Skandinavia, termasuk di Denmark. Kedudukan Ombudsman Denmark atau dikenal sebagai Folketingets Ombudsmand, lembaga tersebut menjadi salah satu lembaga penting dalam sistem ketatanegaraan disana. Sedangkan di Indonesia keududukannya kurang mendapat perhatian. Perbedaan inilah yang membuat penulis tertarik untuk membandingkannya. Pendekatan yang digunakan dalam penulisan ini menggunakan pendekatan mikro jenis bodies of norm, yaitu perbandingan hukum yang menggunakan Undang-Undang sebagai dasar untuk melakukan perbandingan, yang dipakai adalah Undang-Undang Nomor 37 Tahun 2008 tentang Ombudsman Republik Indonesia dibandingkan dengan The Ombudsman Act Denmark. Sedangkan untuk metode perbandingan hukum menggunakan analytical method. Hasil dari penelitian ini adalah untuk dilakukan rekonstruksi hukum pada Undang-Undang Nomor 37 Tahun 2008 tentang Ombudsman Republik Indonesia dengan mengadopsi dari apa yang ada di The Ombudsman Act Denmark. harapannya adalah eksistensi ORI begitu disegani dan rekomendasi dari ORI tidak sekadar mengikat secara moral melainkan mengikat secara hukum.